Augmenting Fertility in Anestrus and Subestrus Cows with Hormonal Interventions and Their Effect on Blood Biochemical Profile - Kumar, Rajesh; Butani, Maganlal Gopalbhai; Kavani, Fulabhai Shambhubhai; Dhami, Arjan Jivrajbhai (The Indian Journal of Animal Reproduction, 2022)
A study was carried out on forty-four problem breeder cows to evaluate the therapeutic efficacy of GnRH and PGF2α for estrus induction response, treatment to estrus induction interval and conception rate and its effect on biochemical profile.  Thirteen true anestrus cows were treated with GnRH (Inj. Receptal, 2.5 ml, IM, once), twenty three subestrus cows were treated with PGF2α (PGF2α, Inj. Estrumate, 2 ml, IM, once) and eight animals kept as untreated anestrus control. The estrus induction response, treatment to estrus induction interval, overall conception rate and service per conception in GnRH treated, PGF2α treated and positive control cows were 84.62%, 28.27±6.46 days, 72.73%, 3.13; 91.30%, 3.52±0.46 days, 71.43%, 2.53 and 50%, 48.25±10.8 days, 50%, 3.5 respectively. The plasma P4 level was significantly lower in all three groups as compared to other two periodic values (d-0 & d-20-22 post AI) which were due to luteal demise. The mean serum total protein was significantly (p
Keywords: Anestrus; Biochemical profile; Cows; Hormone; Subestrus